Estudo histológico e imunoistoquímico do sistema nervoso central de cães naturalmente infectados por Leishmania (Leishmania) chagasi - Ikeda, Fabiana Augusta [UNESP]; Laurenti, Márcia Dalastra; Corbett, Carlos Eduardo; Feitosa, Mary Marcondes [UNESP]; Machado, Gisela Fabrino [UNESP]; Perri, Silvia Helena Venturoli [UNESP] (My University, 2007)
The present study aimed to characterize the histopathological alterations and to detect, by immunohistochemistry, the presence of amastigote forms of Leishmania in CNS tissue of dogs with and without neurological clinical signs of the disease. Two groups of animals were used: the first was composed of 18 dogs with visceral leishmaniasis without clinical evidence of neurological involvement, and the second, composed of 21 dogs with visceral leishmaniasis and neurological symptoms. The most frequent histopathological alterations found in the CNS of dogs of both groups were neuronal degeneration with neuronophagia, gliosis, leptomeningitis, vascular congestion, presence of perivascular lymphoplasmacytic infiltrate and areas of focal microhemorrhage. Antigen labeling for whole forms of Leishmania amastigotes was not observed in any fragment of the CNS of the dogs of either groups; however, most of them presented labeling of blood vessels walls, which suggests the presence of circulating parasite antigens.
Histological and immunohistochemical study of the central nervous system of dogs naturally infected by Leishmania (Leishmania) chagasi
Keywords: Central nervous system; Dogs; Histopathology; Immunohistochemistry; Leishmania chagasi; Animalia; Canis familiaris; Leishmania donovani chagasi